Development of Tortoise Beetle Pest Populations (Coleoptera: Chrysomelidae) on Several Cultivars of Sweet Potato (Ipomoea batatas L.) - Handayani, Ayudina; Supeno, Bambang; Haryanto, Hery (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Tortoise beetles are pests that can inhibit growth and cause damage to sweet potato plants, especially to the leaf organs. This damage will vary depending on the cultivar used as the host. The purpose of this study was to determine the development of tortoise beetle pest populations on several sweet potato cultivars (Ipomoea batatas L.) commonly found in West Lombok. The design used in this research activity was a Randomized Block Design (RBD) with six sweet potato cultivar treatments (K). These treatments were Lato-lato (K1), Cilembu (K2), Thailand (K3), Potato (K4), Ase (K5), and Ungu (K6). Each treatment was repeated 4 times to obtain 24 experimental units. The results of the study found three species of tortoise beetle pests, namely Lactoptera Tredecimunctata, Cassida Sircumdata, and Asphidimorpha Santaecrucis. The development of the tortoise beetle pest population showed fluctuations in all sweet potato cultivars from 5 to 15 WAP. Cultivars Ase, Thailand, and Potato tended to be more susceptible compared to the other three treatments (Purple, Lato-lato, and Cilembu). The intensity of tortoise beetle pest attacks fluctuated, and the Potato cultivar tended to show the highest attack compared to other cultivars.